Hvordan analysere sociale differentieringer? - Jensen, Sune Qvotrup (Women, Gender & Research, 2006)
The current Danish reception of the concept of intersectionality has largely been of a poststructuralist bend. However, the history of the concept is not necessarily as tightly related to poststructuralist theory as often assumed. Although the contributions produced by this reception must be recognised, the poststructuralist version of intersectionality is problematic from a specific sociological position. When social categories are presented as something people do, the reality of social differentiation is downplayed. Poststructuralist thinking rests on an inadequate conception of the material, as this form of thought tends to theorize this as another type of discourse or as a consequence of discourse. It furthermore tends to homogenise the logics underlying different forms of social differentiation. These points are illustrated by the works of Bourgeois and Wacquant where socio-cultural interpretations are transformed by changes on a material level.